Polypyrrole-modified magnetic multi-walled carbon nanotube-based magnetic solid-phase extraction combined with dispersive liquid–liquid microextraction followed by UHPLC-MS/MS for the analysis of sulfonamides in environmental water samples. (12th November 2018) - Yuan, Xucan; Wu, Di; Liu, Chu; Li, Xianhui; Xiong, Zhili; Zhao, Longshan
Abstract : Polypyrrole modified magnetic multi-walled carbon nanotubes were prepared and applied as an efficient adsorbent for magnetic solid-phase extraction. Abstract : A sensitive and accurate analytical method, magnetic solid-phase extraction combined with dispersive liquid–liquid microextraction followed by ultra-high performance liquid chromatography-tandem mass spectrometry, was established for the simultaneous quantification of eight sulfonamide antibiotics in environmental water samples. In this study, a magnetic nanocomposite, polypyrrole-modified magnetic multi-walled carbon nanotubes, was prepared, characterized and applied as an efficient adsorbent for magnetic solid-phase extraction. The synthetic material exhibited satisfactory adsorption capacity for sulfonamides. Moreover, the sample pretreatment-combined technology of magnetic solid-phase extraction and dispersive liquid–liquid microextraction exhibited better purification ability than only magnetic solid-phase extraction. Furthermore, the various extraction parameters affecting the extraction efficiency were thoroughly optimized. Under the optimized conditions, high sensitivity was achieved with method detection limits in the range of 1.02–2.97 ng L −1 and method quantitation limits in the range of 3.05–9.89 ng L −1 . The recovery of eight sulfonamides in five environmental water samples was in the range of 78.3–95.6% and the relative standard deviations were no more than 8.5%. Finally, the method was successfully applied to the analysis of sulfonamides in real environmental water samples (river water, lake water, influent wastewater, effluent wastewater and farm wastewater). Accordingly, the newly established method is reliable for monitoring sulfonamide residues in complex environmental matrices, which has great significance for evaluating the effects of sulfonamide residues on humans and the ecosystem.